2010
DOI: 10.1108/02632771011083694
|View full text |Cite
|
Sign up to set email alerts
|

Management of client requirements for design and build projects in the construction industry of Hong Kong

Abstract: Purpose -This paper aims at investigating the prevailing practice of managing client requirements for design and build (D&B) construction projects in Hong Kong. It attempts to evaluate the limitations and addresses the need for a practical framework for facilitating the implementation of client requirements management within the industry.Design/methodology/approach -Two research instruments were used in this paper:semi-structured interviews and case studies.Findings -The study revealed that the limitations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Not all relevant parties are involved to contribute at the right time of the projects (Kamara and Anumba, 2000;Yu, 2007;and Yu et al, 2010a). (6) Insufficient time to work out a good structure for RsM -Getting the requirements structured correctly and precisely takes time because the structure depends on what kinds of users there are, on what each kind of user expects the project to fulfill, and on the nature of the constraints.…”
Section: Literature Review Problems and Solutions Of Rsmmentioning
confidence: 99%
“…Not all relevant parties are involved to contribute at the right time of the projects (Kamara and Anumba, 2000;Yu, 2007;and Yu et al, 2010a). (6) Insufficient time to work out a good structure for RsM -Getting the requirements structured correctly and precisely takes time because the structure depends on what kinds of users there are, on what each kind of user expects the project to fulfill, and on the nature of the constraints.…”
Section: Literature Review Problems and Solutions Of Rsmmentioning
confidence: 99%
“…Although there is abundant literature on the management of stakeholders' needs in general (Smith and Love, 2004;Takim, 2009;Yuan et al, 2010;Jennings et al, 2013;Yang and Shen, 2014), typical construction processes lack practical frameworks for specifically managing the owner´s needs (Shen et al, 2004;Yu et al, 2010;Chua and Yeoh, 2011;Yu and Shen, 2013). In most cases, owners express their needs on the basis of their previous construction experience but the reliability of this strongly decreases with the project complexity (Kamara et al, 1999 and2000b;Lima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2012) went a step further and relate quality to the definition of project requirements and its management. Nonetheless, Yu et al (2010) concluded that managing the owner´s needs for design and construction phases still raised a number of practical difficulties. Shen et al (2004) proposed a very interesting framework for defining client requirements at the early start of the design phase of a building project.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations